The clinical effect of hippotherapy on gross motor function of children with Cerebral Palsy - K Litlle; N Nel; V Ortell; H van Wyk; M Badenhorst; Q Louw (AOSIS, 2013)
Background: Cerebral palsy (CP) is the most common cause of physical disability affecting gross motor function (GMF ) in early childhood. Hippotherapy is a treatment approach aimed at improving GMF in children with CP. Several systematic reviews have been published showing an improvement in Dimension E of the Gross Motor Function Measure (GMFM ) after hippotherapy. However, these reviews failed to evaluate the clinical effect of hippotherapy in improving GMF in children with CP. Objective: To critically appraise the evidence of hippotherapy to ascertain whether it is a clinically meaningful approach for children with CP. Methodology: Five computerised bibliographic databases were searched. Predetermined inclusion and exclusion criteria were set. The PEDro scale was used to assess the quality of the studies. A revised JBI Data extraction tool was used to extract data from the selected articles. Revman© Review Manager Software was used to create forest plots for comparisons of results. Results: All studies used the GMFM as an outcome measure for gross motor function. The added benefit of hippotherapy is a minimum 1% and a maximum 7% increase on the GMFM scores. However, all 95% confidence intervals (CI ) around all the mean differences were insignificant. Conclusion: The clinical effect of hippotherapy on the GMF of children with CP is small. Larger studies are required to provide evidence of the effect of hippotherapy within this population.